Assessing Quality of Referrals to a Community-Based Chronic Pain Clinic - Angela Mailis; Amna Rafiq; Amol Deshpande; S. Fatima Lakha (Taylor & Francis Group, 2024)
Introduction Because patients with chronic pain are complex, with significant medical and psychiatric comorbidities, referrals to specialty pain clinics are often necessary. The present study explores the quality of information submitted and the profile of referring physicians associated with rejected patient referrals by a community pain clinic.Methods A retrospective cross-sectional study was conducted on a series of consecutive new patient referrals rejected by a noninterventional community pain clinic (November 2021-June 2022). Data were collected on the reasons for rejected referrals and physicians responsible for these referrals using the public database of the College of Physicians and Surgeons of Ontario.Results During the study period, 120 new referrals made by 99 physicians (88% primary care providers, or PCPs; male : female ratio 1:1.2; 53% Canadian university graduates) were rejected because of inadequate information (62%) or because they were inappropriate (38%). Only 46% of the rejected referrals were resubmitted within a median of 7 days (range 0-96 days) and accepted. Half of the non-resubmitted referrals could have been accepted if the referring provider had sent in the missing information.Conclusion A significant number of referrals to our pain clinic (primarily from PCPs) are rejected for mainly avoidable reasons. The process of rejected referrals and resubmissions requires 92 to 126 h of additional staff time/year. Without additional health care resources, our study highlights simple but effective improvements in the referral process that could facilitate patient care, avoid unnecessary delays, and decrease possible sources of patient complaints.